The Concept of Islamic Boarding School Education Development According to K.H. Abdurrahman Wahid - Ahmad Maulana Safarudin (COMPETITIVE: Journal of Education, 2022)
This study aims to determine the concept of Islamic boarding schools in general to find out the views of KH. Abdurrahman Wahid on the concept of advancing pesantren education. In this study, researchers used a literature study using descriptive research methods, namely from all the data collected and then analyzed qualitatively. This research concludes that the concept of Islamic boarding school education is the basis of character education by emphasizing the concept of moral education based on the Qur'an and Hadith. That humans are taught to always be good and the best and to be able to prevent bad deeds. The process of learning and teaching in the pesantren environment is not just mastering religious sciences but also the process of forming a view of life, and determining the behavior of the students after they return from the Islamic boarding school to the life of the community. The concept of advancing pesantren put forward by KH. Abdurrahman Wahid namely: encouraging a program of mixing religious and non-religious components in the formal curriculum at Islamic boarding schools, skills programs and community development programs.